GENETIC MAPPING IN BREAST CANCER: QUANTIFICATION OF REQUESTS BY ONCOLOGISTS, MASTOLOGISTS, AND GENETICISTS IN GOIÁS (CIPEEX, 2026)
Introduction: Breast cancer is one of the most impactful neoplasms worldwide as well as in Brazil. Germline mutations in the BRCA1/BRCA2 genes contribute to 5–10% of cases and make genetic mapping a relevant tool for prevention and individualized management. In Goiás, Law No. 20,707/2020 provides for the availability of testing for risk groups, which makes it important to assess its clinical adoption.Objective: To quantify the proportion of oncologists, mastologists, and geneticists in Goiás who have already requested genetic mapping and to identify reasons and barriers to its incorporation into practice.Method: Observational, cross-sectional, and exploratory study. Data collection was carried out through an electronic questionnaire with informed consent; descriptive analysis was performed in spreadsheets. Sociodemographic profile, knowledge, frequency of use, and reasons for requesting or not requesting the test were evaluated.Results: Sixteen physicians participated: 8 oncologists, 7 mastologists, and 1 geneticist; 10 were male, with the predominant age group being 31–40 years. Of the participants, 15 reported being familiar with genetic mapping; 8 used it frequently, 3 sometimes, 3 rarely, and 1 never. The main triggers for requesting the test were diagnosis before the age of 40, direct family history, and triple-negative tumors before the age of 50. Reported barriers included the perception of low cost-effectiveness, insufficient preparation for counseling, and the belief in limited clinical utility.Conclusions: Despite the widespread reported knowledge, only half of the professionals routinely use genetic mapping, indicating a gap between knowledge and practice. Training in genetic counseling, dissemination of therapeutic pathways, and larger studies are recommended to guide local policies.
Keywords: BRCA1 Gene; BRCA2 Gene; Chromosomal Mapping; Breast Neoplasms